OLAHRAGA DAN KEBUGARAN JASMANI (PHYSICAL FITNESS) PADA ANAK USIA DINI - Paiman Paiman (LPMPP Universitas Negeri Yogyakarta, 2009)
AbstractSports and Physical Fitness in Early Age Children. Sports activities areimportant for early age children. Through such activities they can improve theirphysical fitness and the quality of their organs, including the heart, lungs, bloodcirculation, energy metabolism, growth hormones, immune system, and secretionsystem. The improvement will result in the higher quality of their physical andspiritual conditions. Characteristics of good sports activities for early age childrenare that: (1) they provide a variety of movements (multilateral training) in the formof games and competitions, (2) they stimulate the development of all the fivesenses, (3) they develop imagination, and (4) they follow a rhythm/song and astory. Early age childrens physical fitness can be controlled by taking account oftheir body composition, namely by maintaining the balance between the foodintake and the physical activities.Keywords: early age children, sports, physical fitness